The Winter's Tale - Shakespeare, William (Wordsworth Editions Ltd, 1995)
A late romance from William Shakespeare (1564-1616), The Winter's Tale follows the friendship of two kings as it descends into jealousy, charges of adultery, and eventual redemption.
Keywords: Classics (Shakespeare)-Drama (Comedy)